2012
DOI: 10.3109/00016489.2012.656763
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the horizontal vestibulo-ocular reflex in motorized head impulse test is common after vestibular loss

Abstract: The early ipsilesional gain of 0.49 ± 0.21 improved highly significantly to the late gain of 0.79 ± 0.23 (p = 0.0000). The respective asymmetry improved highly significantly from 32 ± 18% to 12 ± 14% (p = 0.0002). Gain or asymmetry recovered at least partially in 80% of the patients. The late high symptom score correlated with low gain (p = 0.043) and high asymmetry (p = 0.018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
2
0
2
Order By: Relevance
“…Similar observations were described by Jutila et al who examined patients with acute vestibular loss using vHIT on day 3 and at 3 months after the occurrence of vestibular symptoms. There was a highly significant improvement in gain from deteriorated to normal values as well as a decrease in previously existing asymmetry (54). Ibrahim et al (55) demonstrated that cochlear implantation had no significant effect on the outcome of vHIT, consistent with our observations.…”
Section: Video Head Impulse Testsupporting
confidence: 91%
“…Similar observations were described by Jutila et al who examined patients with acute vestibular loss using vHIT on day 3 and at 3 months after the occurrence of vestibular symptoms. There was a highly significant improvement in gain from deteriorated to normal values as well as a decrease in previously existing asymmetry (54). Ibrahim et al (55) demonstrated that cochlear implantation had no significant effect on the outcome of vHIT, consistent with our observations.…”
Section: Video Head Impulse Testsupporting
confidence: 91%
“…Other than differing in techniques for recording eye and head movements, the methods in evaluating gain in horizontal VOR differ. Gain can be calculated as the ratio of eye to head acceleration, as the ratio of eye to head velocity, or the ratio of the AUC for eye velocity divided by the AUC for head velocity . In addition, gain can be calculated over different time intervals, such as for several milliseconds before the peak head velocity, several milliseconds before the peak head acceleration, several milliseconds after the head movement onset or while the head and eyes are moving.…”
Section: Discussionmentioning
confidence: 99%
“…Offensichtlich war die GA als Instrument zur Markierung einer einseitigen peripher-vestibulären Störung in der Kohorte nicht geeignet. Beim Vergleich mit der Literatur ist zunächst bemerkenswert, dass sehr unterschiedliche Grenzwerte für eine pathologische GA vorgeschlagen werden, die von 4-40 % reichen [8,19,31,32,[35][36][37]. Dies allein muss die Belastbarkeit einer auf dieser Größe basierenden Aussage in Frage stellen.…”
Section: Vorkommen Von Pathologischen V-kit-parameternunclassified
“…Die Software sollte nur geeignete Kopfimpulse zur Auswertung mit Berechnung des Gain zulassen [27]. Studien mit apparativ kontrollierten Kopfimpulsen konnten diese Probleme nicht zufriedenstellend beheben [33,35].…”
Section: Vorkommen Von Pathologischen V-kit-parameternunclassified